1980
DOI: 10.1055/s-2007-1022065
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Coronary Air Embolism. Assessment of Time Course of Myocardial Ischemia and the Protective Effect of Cardiopulmonary Bypass1

Abstract: In 74 mongrel dogs 0.02 ml air/kg of body weight was injected into the left anterior descending coronary artery (LAD). Forty-three dogs were studied without (group I) and 31 with (group II) extracorporeal circulation (ECC). Time course and extent of myocardial ischemia were assessed by continous thermographic measurements as well as by fluorescence techniques. Coronary air embolism resulted in an immediate decrease of myocardial temperature associated with transmural ischemia. In 31 surviving dogs (72%) of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The time course of events is consistent with findings of experimental air embolism [4]. Depending on the solubility of the gas, the bubbles will keep the arterioles occluded until they are reabsorbed or pushed into the coronary sinus IS].…”
Section: Fig 2 A: Inside a Contrast-filled Plastic Tubing A 3-mm Hasupporting
confidence: 82%
“…The time course of events is consistent with findings of experimental air embolism [4]. Depending on the solubility of the gas, the bubbles will keep the arterioles occluded until they are reabsorbed or pushed into the coronary sinus IS].…”
Section: Fig 2 A: Inside a Contrast-filled Plastic Tubing A 3-mm Hasupporting
confidence: 82%
“…A close correlation was described in animal models. Injection of 0.02 ml/kg of air into the coronary arteries of dogs resulted in a 28% rate of mortality [9]. The surviving animals spontaneously recovered global heart function within 15 min.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…We did not approach this volume in our study. Another study with dogs showed a mortality rate of 28% in dogs after injection of 0.02 mL air/kg of body weight [14]. Other researchers demonstrated increasing cardiac depression in pigs by injecting air bubbles with approximate volumes of 0.002 mm 3 (diameter: 75 µm), 0.014 mm 3 (diameter: 150 µm) or 0.113 mm 3 (diameter: 300 µm) [12].…”
Section: Discussionmentioning
confidence: 97%